The impact of COVID-19 on heat-related ambulance calls and the challenges for emergency medical transport in the Kansai region, Japan: a mixed methods approach - Deng Ke; Dimiter S Ialnazov; Kaoru Takara (IOP Publishing, 2024)
The COVID-19 pandemic, coupled with more frequent and stronger heatwaves, has introduced a novel confluence of challenges. In Japan, emergency medical transport staffs are facing increasing difficulty in distinguishing between COVID-19 and heat stroke at the scene because they share some similar symptoms. This study explored the impacts of the COVID-19 pandemic on heat-related ambulance calls and identifies the challenges faced by local fire departments in the Kansai region of Japan over 2020-2022. Both historical data analysis and an online questionnaire survey were used in this study. We utilized a heat-related ambulance calls prediction model developed in our previous research based on the historical data (2008-2019) to project the expected number of heat-related ambulance calls from 2020 to 2022. Subsequently, we compared expected number and the actual number of daily heat-related ambulance calls to examine the variations of heat-related ambulance calls across six prefectures in the Kansai region. Our findings reveal a significant decrease in the number of heat-related ambulance calls during the COVID-19 pandemic across all Kansai prefectures, ranging from 3.2% to 22.9%. The decline in heat-related ambulance calls can be attributed to shifts in daily routines, such as the increase of remote work and decrease of outdoor exercise. However, it may also be influenced by the strain on the emergency medical resource. Furthermore, this study has also highlighted substantial pressures on local fire departments and emergency medical transport systems during the pandemic. A primary challenge for local fire departments was securing available medical facilities for patients. Improving the efficiency of the emergency medical transport system and enhancing the coordination between emergency medical services and healthcare facilities may offer a more resilient response in future crises.